THE IMPACT OF MULTICULTURAL EDUCATION ON THE DEVELOPMENT OF TOLERANCE CHARACTER OF ELEMENTARY AGE STUDENTS - Idawati, Idawati; Rosmiati, Rosmiati; Syamsuddin, Agustan (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
Background: Various studies on multicultural education have been examined by previous researchers, but the focus on efforts to foster intercultural awareness and tolerance attitudes has not been responded to in a complex manner. Purpose: The purpose of this study is to examine how intercultural awareness education develops student character. Method: This research combines a literature review methodology with a qualitative approach. Result: The research findings show that developing one's character requires consistent work and deep contemplation to arrive at a number of moral judgments which must then be practiced for them to become wise and practical. To form all of these into habits and shape one's character or behavior, it takes time. The family and home, the school environment, and the community must all be involved in the education process. Rebuilding the almost destroyed educational network and the relationship between the three educational contexts is the main step to take. As long as the three educational environments are not harmonious and sustainable, it will never be possible for the nature and character of education to be successfully formed. Given this fact, the strong influence of home, school and society is necessary to help students develop into excellent citizens.